Optimization Design of Modification of Herringbone Star Gear Transmission - Yan Yuesheng; Zhang Xijin; Jia Chao (Jixie chuandong)
Gear modification is an important technique to improve its transmission performance. The herringbone gears are combined with star gear transmissions to form a herringbone star gear transmission,and its modeling method of modified tooth surface as well as computing method of loaded transmission error are researched. With the target of the minimum amplitude of loaded transmission error,the gear modifications are optimized for the sun-star meshing gear pair and the star-ring meshing gear pair respectively. The modifications from optimization are redistributed,and the rationality of the redistribution is verified by the means of TCA and LTCA techniques. The research results provides a theoretical basis for the modification design of a star gear train.